Enhancing Thermal Management in Protective Textiles Using Hydrated Salt as Phase Change Materials (Journal of Fiber Bioengineering and Informatics, 2024)
The thermal properties of textiles are essential for ensuring the comfort of both fabric and clothingsystems. Phase change materials (PCMs), which contain latent heat, play a significant role in this area.As ambient temperature fluctuates, PCMs absorb heat, melt or release heat, and solidify. Throughoutthese melting and crystallizing processes, the temperature of the PCM remains constant. Integratingsuitable PCMs into garments helps maintain a stable temperature within the micro-environment betweenthe garment and the wearer. The effectiveness depends on the quantity of PCMs used. This studysynthesised and evaluated a novel type of nano-capsule containing PCM Glauber’s salt. Advancedtechniques such as Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), andFourier-Transform Infrared Spectroscopy (FTIR) were employed to analyze the developed nano-capsules.Additionally, a finite element model was created to enhance the understanding of the thermal mechanismsin textiles incorporating PCMs. This comprehensive analysis aims to promote the application of PCMs inprotective textiles, contributing to developing next-generation materials that provide thermal regulationand protection for the wearer.
Keywords: Protective Textiles; Temperature Management; Phase Change Materials; Latent Heat; Nano Encapsulation; Finite Element Simulation.